Analisis Penerapan Metode RGEC Guna Menilai Tingkat Kesehatan Perbankan Syariah Tahun 2015-2017 (Studi Kasus Pada PT. Bank Central Asia Syariah) - Ratna Kurnia Sari; Husni Mubarok (BALANCE: Economic, Business, Management and Accounting Journal, 2020)
In the economic system, banking has an important role in, supporting the economic progress of a country. In Indonesia alone, banking is known to be of two types, namely conventional banks and Islamic banks. Conventional banks usually refer to the interest system, which is most likely to be affected by the crisis. Whereas Islamic banks refer more to the profit sharing system and approach the community and reduce the risk or monetary fluctuation. The purpose of this study was to look at the health level of PT. Bank Central Asia Syariah using the RGEC method which includes risk profile, good corporate governance, earning and capital for 3 years. The result of the study in general showed that the health level of PT. Bank Central Asia Syariah in term of RGEC in 2015-2016 is in the position of composite rank 3 in a fairly healthy condition. Whereas in 2017 it was in the position of composite rank 2 in a healthy state. And to maintain public trust as the owner of the funds, stakeholders, and the government as supervisors, PT. Bank Central Asia Syariah is expected to be able to improve the ability of assets, capital management, and operational income, so that the quality of bank profits can be maintained and even improved. Keywords                   : Analysis, PT. Bank Central Asia Syariah, RGEC Method